2014
DOI: 10.2478/pjvs-2014-0089
|View full text |Cite
|
Sign up to set email alerts
|

The effects of subcutaneous and intraocular administration of class B ODN CpG in chicken on the expression of TLR21, IFN-γ and IL-1β

Abstract: The synthetic unmethylated oligodeoxynucleotides with CpG motifs (CpG ODN) were shown to activate Toll-like receptor 21 (TLR21) and stimulate the innate and adaptive immune system. In this study we tested the expression of TLR21, interferon (IFN)-γ and interleukin (IL)-1β mRNA in the blood after subcutaneous and intraocular application of the class B CpG ODN in chicken. The relative expression of mRNA of TLR21, IFN-γ and IL-1β were quantified at 3, 6, 12, 24 and 72 h post-stimulation. The study revealed that I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Interestingly, TLRs recognizing others PAMPs are also upregulated, such as TLR2, TLR3, TLR4, TLR5, and TLR6. Of note, TLR21, the chicken TLR9, was detected but surprisingly not differentially expressed ( Chrząstek and Wieliczko, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TLRs recognizing others PAMPs are also upregulated, such as TLR2, TLR3, TLR4, TLR5, and TLR6. Of note, TLR21, the chicken TLR9, was detected but surprisingly not differentially expressed ( Chrząstek and Wieliczko, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…chTLR21 expression could be induced by stimulation with CpG-ODN. Inoculation of class B CpG ODN subcutaneously potently upregulated the expression of TLR21, interleukin (IL)-1β, and interferon (IFN)-γ mRNA in the blood cells (Chrzastek and Wieliczko, 2014). Another study conducted in vitro indicated that the mRNA expression levels of TLR21 and IFN-γ were substantially increased by Class B CpG ODN stimulation at 1 h post-stimulation in a concentration-dependent manner, while this phenomenon only exited in HG cells isolated from young birds .…”
Section: Chtlr21mentioning
confidence: 99%